Turismo religioso na cidade da santa: a percepção da comunidade sobre a construção do Complexo Turístico e Religioso Alto de Santa Rita, Santa Cruz/RN - Farias, Mayara Ferreira de (2013)
The general objective of this study was to analyze the city of Santa Cruz cope with the impacts of the changes caused by the insertion of religious tourism with the construction of the Tourist Complex Religious Alto de Santa Rita, and specific objectives: to identify the economic activities from building the Tourist Complex Religious Alto de Santa Rita with the monument of Santa Rita; describe the research scenario to respect the traditions, rituals and spatial organization of the city and to evaluate the impacts through construction of movement by Religious Tourism Complex human capital and economic development fostered by Religious Tourism. To this end, we used the methods of application of Questionnaires and interviews, as well as the method was conducted participant observation, individual and systematic, having exploratory held through a correlational analysis regarding the impacts by inserting Tourism religious elsewhere. Was performed also discourse analysis of speeches Stakeholder city of Santa Cruz / RN for understanding the local reality. Literature search was performed readings of books, articles, theses and dissertations dealing with the issue, it was necessary to use data from websites. As for the media research field was qualitative. At the end of the study, it was concluded that the city of Santa Cruz suffered socio-economic and cultural, as a result, especially the lack of a previously developed tourism planning